Environmental Federalism: A Survey of the Empirical Literature - Daniel L. Millimet (Institute for the Study of Labor (IZA), 2013)
Environmental federalism refers to the debate over the 'optimal' level of government at which to delegate environmental policymaking. Although this issue receives widespread attention across the globe, opinions run the gamut. The diversity of views plays out in practice as well as different federations have 'resolved' the issue differently. With the United States alone, environmental authority has oscillated between periods of relatively greater centralized and decentralized control. This article seeks to accomplish two objectives in order to advance the literature. The first objective is to provide a brief overview of the two primary theoretical frameworks Tiebout (1956) and models of interjurisdictional competition used to explore the effects of the decentralization of policy decisions such as taxes, expenditures, environmental standards, etc. The reason for doing so is to illuminate the issues that play a fundamental role in conclusions regarding the 'optimal' allocation of environmental authority. The second objective is to then provide a comprehensive survey of the relevant empirical literatures. By doing so, the goal is to limit the scope of the debate over environmental federalism moving forward, as well as make clear where the gaps in empirical knowledge exist.
Keywords: H77; Q58; 330; environmental regulation; federalism; Tiebout; interjurisdictional competition